Will previous antimicrobial therapy reduce the positivity rate of metagenomic next-generation sequencing in periprosthetic joint infections? A clinical study - Hao, Linjie; Bian, Weiguo; Qing, Zhong; Ma, Tao; Li, Hui; Xu, Peng; Wen, Pengfei (Frontiers in Cellular and Infection Microbiology, 2024)
Background Metagenomic next-generation sequencing (mNGS) is a culture-independent massively parallel DNA sequencing technology and it has been widely used for rapid etiological diagnosis with significantly high positivity rate. Currently, clinical studies on evaluating the influence of previous antimicrobial therapy on positivity rate of mNGS in PJIs are rarely reported. The present study aimed to investigate whether the positivity rate of mNGS is susceptible to previous antimicrobial therapy. Methods We performed a prospective trial among patients who undergone hip or knee surgery due to periprosthetic joint infection (PJI) to compare the positivity rate of culture and mNGS between cases with and without previous antimicrobial therapy, and the positivity rates between cases with different antimicrobial-free intervals were also analysed. Results Among 131 included PJIs, 91 (69.5%) had positive cultures and 115 (87.8%) had positive mNGS results. There was no significant difference in the positivity rate of deep-tissue culture and synovial fluid mNGS between cases with and without previous antimicrobial therapy. The positivity rate of synovial fluid culture was higher in cases with previous antimicrobial therapy. The positivity rates of mNGS in synovial fluid decreased as the antimicrobial-free interval ranged from 4 to 14 days to 0 to 3 days. Conclusion mNGS is more advantageous than culture with a higher pathogen detection rate. However, our data suggested that antimicrobial agents may need to be discontinued more than 3 days before sampling to further increase the positivity rate of mNGS for PJIs.